CHALLENGES FACING ISLAMIC BANKING IN IRAN: EVALUATION AND POLICY IMPLICATIONS - Hossein Meisamy; Hassan F. Gholipour (Journal of Islamic Monetary Economics and Finance, 2020)
Iran is one of the few countries that has instituted shariah-compliant banking nationwide and does not have a conventional banking sector. However, since the Riba-Free Banking Act (RFBA) was passed and put into practice in 1983, the Iranian Islamic banking system has experienced some significant challenges and shortcomings. The main purpose of this paper is to identify the various impediments facing the Iranian Islamic banking industry and to suggest a prioritized listing of these challenges. To achieve this goal, a three-round Delphi study (a method designed to aid consensus building) is used to determine the major challenges and rank them based on relative importance. The research panel consulted consists of 32 Iranian Islamic banking experts with in-depth knowledge and experience. The results show that the top five challenges to the Islamic banking system in Iran are (1) the governmental attitude towards Islamic banking; (2) lack of competition; (3) not revising the law (RFBA); (4) lack of shariah supervision; and (5) lack of accounting and auditing standards. This paper contributes to the literature addressing Islamic banking by critically analysing the more than three decades of Iranian experience in implementing shariah-compliant banking.